AB0946 Improvements in work productivity with up to 104 weeks of apremilast monotherapy: results from a phase 3b, randomised, controlled study in biologic-naÏve subjects with active psoriatic arthritis. (12th June 2018) - Mease, P.J.; Gladman, D.D.; Davenport, E.K.; Zhou, X.; Guerette, B.; Teng, L.; Kaura, S.; Nash, P.
Abstract : Background: Psoriatic arthritis (PsA) patients may experience disease manifestations across multiple domains and impaired functioning in daily activities at home and work. The phase 3b ACTIVE study is evaluating the efficacy of apremilast (APR) monotherapy in biologic-naïve subjects with active PsA who may have had exposure to 1 prior conventional DMARD. Objectives: To assess work productivity through Week 104. Methods: Subjects were randomised (1:1) to receive APR 30 mg BID or placebo (PBO). Subjects who did not improve by ≥10% in swollen and tender joint counts at Week 16 were eligible for early escape. At Week 24, all remaining PBO subjects were switched to APR. Work productivity and activity impairment were assessed at baseline (BL) and Week 16 using the 6-item, self-administered Work Productivity and Activity Impairment Questionnaire: Psoriatic Arthritis (WPAI:PsA). WPAI:PsA includes 4 subscale scores (Absenteeism, Presenteeism, Work Productivity Loss, and Activity Impairment), each ranging from 0% to 100%; higher scores indicate greater impairment. Work-related subscales were evaluated only among employed subjects, while activity impairment was evaluated among all subjects, regardless of employment. Correlations were examined at Week 16 between WPAI:PsA subscale scores and the SF-36v2 domain scores for Physical Functioning (PF), Bodily Pain (Pain), and Vitality (VIT), as well as associations with ACR20 response. Improvement in work productivity was assessed through Week 104. Results: BL characteristics were similar between APR and PBO subjects with WPAI:PsA scores included in this analysis. At Week 16, APR significantly improved work productivity and the ability to carry out daily activities vs PBO, with significantly greater mean improvements observed in the overall Work Productivity Loss (p=0.001) and Activity Impairment (p<0.001) scores (table 1). Estimated mean change in the Absenteeism score was similar with APR vs PBO (p=0.679). By contrast, the Presenteeism score showed significant improvement with APR vs worsening with PBO (−10.8% vs 4.1%; p=0.002). At Week 16, statistically significant correlations were observed between WPAI:PsA subscale scores (except Absenteeism) and the SF-36v2 domain scores for PF, Pain, and VIT, as were associations with ACR20 response. Among subjects randomised to APR at BL, improvements in Week 16 WPAI:PsA subscale score were generally maintained through Week 104 in those continuing APR. Results are from an analysis of covariance model, adjusted with BL WPAI: PsA subscale score, BL prednisone use (yes/no), and previous DMARD use (yes/no). LS mean is estimated using the observed margins of the covariates. WPAI: PsA scores were evaluated for subjects with values at both BL and Week 16. Absenteeism, Presenteeism, and Work Productivity Loss were evaluated only among employed subjects. Activity Impairment scores were evaluated among all randomised subjects with scores at BL and Week 16, regardless of employment status. CI=confidence interval; LS=least square. Conclusions: In biologic-naïve subjects with PsA, APR monotherapy contributed to an overall improvement in work productivity at Week 16, which correlated with SF-36v2 PF, Pain, and VIT scores and was associated with ACR20 response; improvements in WPAI:PsA subscale scores were generally maintained to Week 104. Disclosure of Interest: P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, and UCB, E. Davenport: None declared, X. Zhou: None declared, B. Guerette Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, S. Kaura Employee of: Celgene Corporation, P. Nash Grant/research support from: Celgene Corporation